Competitiveness in the Baltics in the Run-Up to EU Accession. (IMF Staff Country Reports; Country Report ;, 2003)
This paper analyzes competitiveness in the Baltics in the run-up to European Union accession. Several factors appear to have driven movements in equilibrium real exchange rates in the Baltics since the start of the transition process. In the earlier years of transition, price liberalization, increased demand for services and other nontradables, and shifts in domestic production and exports toward higher valued-added products contributed to real appreciation through higher measured inflation. The strength of the real appreciation during these years appears to also reflect the correction of an initial undervaluation of exchange rates.